Silicon Effects on Resistance of St. Augustinegrass to Southern Chinch Bugs and Plant Disease - Alan L. Wright; Ron Cherry; Huangjun Lu; Pamela Roberts (EDIS)
Silicon (Si) is the second most common element on earth, but it is not considered an essential element for plant growth. However, a growing body of evidence has shown that Si can enhance plant resistance to insect pests. This 5-page fact sheet reports the results of a study to determine if silicon applications to St. Augustinegrass varieties increase the silicon in the plants and how this increased silicon affects development and survival of southern chinch bugs as well as development of plant diseases. Written by Alan L. Wright, Ron Cherry, Huangjun Lu, and Pamela Roberts, and published by the UF Department of Soil and Water Science, September 2013.